ANALYSIS OF BKD SAVINGS AND LOAN ADMINISTRATION INFORMATION SYSTEM - hanum dwi septiani (Media Jurnal Informatika, 2025)
Savings and Loan Cooperative (KSP) of Village Credit Agency (BKD) Kaligayam Unit plays an important role in supporting the rural economy through microfinance services, such as saving funds and providing loans. However, the administration system currently used is still manual and not integrated, resulting in various obstacles such as recording errors, late reporting, and the risk of data loss. This study aims to analyze the ongoing savings and loan information system, identify weaknesses in the administration process, and provide recommendations for designing a more effective and efficient digital system. The research methods used are direct observation, interviews with related parties, and literature studies. The results of the analysis show that system digitalization is needed to support service improvements, both in terms of recording accuracy, service speed, and customer data security. The proposed system will later be designed to be easy to use by officers, support automatic reporting, and have appropriate access rights settings. With the implementation of a computerized information system, it is hoped that cooperative management will become more modern, transparent, and able to compete with other financial institutions.